Rates and Risk Factors of Revision Arthroscopy or Conversion to Total Knee Arthroplasty Within 1 Year Following Isolated Meniscectomy - Avinesh Agarwalla, M.D; Anirudh K. Gowd, M.D; Joseph N. Liu, M.D; Nirav H. Amin, M.D; Brian C. Werner, M.D (Elsevier, 2020)
Purpose: To identify the rates of and risk factors for revision arthroscopy and conversion to total knee arthroplasty (TKA) within 1 year of isolated meniscectomy. Methods: Humana and Medicare national insurance databases were queried for patients who underwent isolated meniscectomy. Patients who underwent revision arthroscopy or TKA within 1 year postoperatively were identified by International Classification of Diseases Procedural Codes, Ninth Revision, and Current Procedural Terminology codes. Multivariate binomial logistic regression analysis was used to identify risk factors, and adjusted odds ratios (ORs) and 95% confidence intervals (Cis) were calculated, with P < .05 considered significant. Results: A total of 13,142 patients and 407,888 patients underwent isolated meniscectomy in the Humana and Medicare databases, respectively. Of the patients, 395 (3.01%) and 3,770 patients (0.92%) underwent revision arthroscopy, and 629 patients (4.79%) and 38,630 patients (9.47%) underwent TKA within 1 year of meniscectomy in the Humana and Medicare databases, respectively. Obesity (Humana: OR = 1.33, P = 0.003; Medicare: OR = 1.10, P < 0.001) and age < 20 years (Humana: OR = 2.64, P = 0.022), 20-29 years (Humana: OR = 3.30, P = 0.002), 40-49 years (Humana: OR = 3.80, P < 0.001), 50-59 years (Humana: OR = 1.99, P = 0.027), and < 64 years (Medicare: OR = 1.74, P < 0.001) were risk factors for revision arthroscopy. Obesity (Humana: OR = 1.64, P < 0.001; Medicare: OR = 1.37, P < 0.001), morbid obesity (Medicare: OR = 1.20, P < 0.001), age 70-74 (Medicare: OR = 1.12, P < 0.001), 75-79 (Medicare: OR = 1.25, P < 0.001), 80-84 (Medicare: OR = 1.20, P < 0.001), and concomitant osteoarthritis (Humana: OR = 1.42, P < 0.001; Medicare: OR = 1.46, P < 0.001) were risk factors for conversion to TKA. Conclusions: Medicare and Humana databases showed that 0.92%-3.01% and 4.79%-9.47% of patients undergo revision arthroscopy or conversion to TKA within a year of isolated meniscectomy. Obesity was a risk factor for early revision arthroscopy and conversion to TKA, whereas concomitant osteoarthritis was a risk factor for conversion to TKA. Level of Evidence: Level III, retrospective comparative trial.